2013
DOI: 10.1371/journal.pone.0075422
|View full text |Cite
|
Sign up to set email alerts
|

Body Fineness Ratio as a Predictor of Maximum Prolonged-Swimming Speed in Coral Reef Fishes

Abstract: The ability to sustain high swimming speeds is believed to be an important factor affecting resource acquisition in fishes. While we have gained insights into how fin morphology and motion influences swimming performance in coral reef fishes, the role of other traits, such as body shape, remains poorly understood. We explore the ability of two mechanistic models of the causal relationship between body fineness ratio and endurance swimming-performance to predict maximum prolonged-swimming speed (Umax) among 84 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 91 publications
(106 reference statements)
1
54
1
Order By: Relevance
“…Groups or species with small sample sizes ( n < 15) were not included in the correlation tests but were included in the predictive models and the general presentation of results (Table and Figure ). Many studies have tested morphological traits as predictors of dispersal and swimming capacities (Cui et al, ; Fisher et al, ; Fisher & Hogan, ; Leis et al, ; Raventós, ; Teichert et al, ; Walker et al, ; Wilson & Meekan, ). Our observations, aligned with previous results, suggest that fish larval morphologies are better predictors of swimming capacity than their taxonomic identity (Fisher et al, ; Fisher & Bellwood, ; Fisher & Hogan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Groups or species with small sample sizes ( n < 15) were not included in the correlation tests but were included in the predictive models and the general presentation of results (Table and Figure ). Many studies have tested morphological traits as predictors of dispersal and swimming capacities (Cui et al, ; Fisher et al, ; Fisher & Hogan, ; Leis et al, ; Raventós, ; Teichert et al, ; Walker et al, ; Wilson & Meekan, ). Our observations, aligned with previous results, suggest that fish larval morphologies are better predictors of swimming capacity than their taxonomic identity (Fisher et al, ; Fisher & Bellwood, ; Fisher & Hogan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two morphometric ratios were then obtained from these measurements: fineness ratio (ratio between standard body length and maximum body depth) and caudal peduncle depth factor (ratio between least depth of caudal peduncle and maximum body depth). Both morphological ratios have been previously used as predictors of swimming ability and efficiency (Fisher & Hogan, ; Ohlberger et al, ; Scarnecchia, ; Walker et al, ; Webb, ).…”
Section: Methodsmentioning
confidence: 99%
“…Elsewhere, Leris et al (2013) quantified body shape variations between the sexes of D. rerio and reported that females had deeper body depth and width compared with males. Walker et al (2013) demonstrated that shallower body depth is thought to reduce drag during sustained swimming and thus is favoured in open water (pelagic) habitat and, in contrast, deeper body depth is also thought to increase manouverability and boost swimming speed, and thus is favoured in habitat with many hiding places. Therefore, sexual dimorphism of the observed species recorded in body depth in H. fasciatus from the Great Kwa River may probably have resulted as an adaptation for strong river current and defending of territory.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the dimorphic patterns of body depth and standard length between sexes are expected to contribute to differing locomotor potential between female and male individuals of this species. Some authors have reported that body shape traits contribute to performance variations (Langerhans and Reznick, 2010;Walker et al, 2013), prolonged swimming speed and associated morphological performance (Arnold, 1983(Arnold, , 2003Walker, 2007). Overall, the positive relationship between the right pectoral fin and increased gonad weight in S. melanotheron suggests that larger pectoral fins in females were more likely to be primarily affiliated with reproductive activity, while larger body depth of female H. fasciatus and its highlighted role in sexual dimorphism of this species is more suggestive of being primarily for locomotor function.…”
Section: Discussionmentioning
confidence: 99%